Developing Introverted and Extroverted Students’ Descriptive Writing through Kalesang Values and FRESH Technique - Natalia Manuhutu; Rudi Hartono; Abdurrachman Faridi; Zulfa Sakhiyya (Yayasan Keluarga Guru Mandiri, 2025)
This study examines the role of Maluku local wisdom, specifically